Pengaruh Pembelajaran Steam Terhadap Kreativitas Anak Usia 5-6 Tahun - Yulinda Magdalena Humau; Yalen Neonleni; Muni Hermina; Mia Laosan; Maria Banunaek; Febi Priska Huki; Fredericksen Victoranto Amseke (Jurnal E-MAS (Edukasi dan Pembelajaran Anak Usia Dini), 2026)
This study aims to determine the effect of STEAM learning on the creativity of children aged 5-6 years at PAUD Moria Liliba Kupang City. The research method used is quantitative with ex-post facto type, with 20 children as respondents selected through total sampling technique. The research instruments used were the STEAM Learning Implementation Scale and Early Childhood Creativity Scale which had been tested for validity and reliability. Data analysis was performed using simple linear regression with the SPSS version 26.0 program. The results showed that the implementation of STEAM learning was mostly in the low category (50%), while children's creativity was dominated by the moderate category (45%). The hypothesis test proves that there is a positive and significant effect of STEAM learning on children's creativity with F=4309.800 and p=0.000. The influence coefficient is 0.330 and the R Square value is 0.207, indicating that about 20.7% of the variation in children's creativity can be explained by STEAM learning. Based on the research results, it is suggested that teachers optimize the implementation of STEAM learning so that the creative potential of children aged 5-6 years can develop optimally.